Penerapan Multimetode Berbasis Matriks Pada Seleksi Penerimaan Calon Asisten Labor - Rahimullaily, Rahimullaily; Maltaf, Lakry (Pendidikan Matematika Universitas PGRI Yogyakarta, 2017)
AbstractThe survey was conducted in the Computer Laboratory of Information System of STMIK Indonesia of Padang. The Head of Laboratory determined some criteria in selecting of acceptance of labor assistant candidate. These criteria were the Candidate Application Form (FPC), the Competitive Achievement Index (GPA), the test score, the English test score, and the interview results. The head of the laboratory performed the process of calculating the criteria value by summing the value of each criterion in deciding who was accepted as a labor assistant. Who has the highest number of criteria, then he/she was selected as a laboratory assistant. This allows occurring the less ideal decision because of the basis of decision-making based on calculations not using special calculation method yet to decision making. Therefore, the researcher performed the process of calculating of the criteria value by using a matrix-based calculation method that was Simple Additive Weighting Â (SAW) method and Analytic Hierarchy Process (AHP) method. The results of this study are expected to assist the Head of Labor in deciding the laboratory assistant based on the standard calculation as decision making.Â Keyword: SAW, AHP, Labor Assistant Candidate